Zero the hero: Evidence for involvement of the ventromedial prefrontal cortex in affective bias for free items. (March 2023) - Lenglin, V.; Wong, S.; O'Callaghan, C.; Erzinçlioğlu, S.; Hornberger, M.; Lebouvier, T.; Piguet, O.; Bourgeois-Gironde, S.; Bertoux, M.
Abstract: Recent evidence from psycho-economics shows that when the price of an item decreases to the extent that it becomes available for free, one can observe a remarkable increase of subjective utility toward this item. This phenomenon, which is not observed for any other price but zero, has been termed the zero-price effect (ZPE). The ZPE is attributed to an affective heuristic where the positive affect elicited by the free status of an item provides a mental shortcut biasing choice towards that item. Given that the ZPE relies on affective processing, a key role of the ventromedial prefrontal cortex (vmPFC) has been proposed, yet neuroscientific studies of the ZPE remain scarce. This study aimed to explore the role of the vmPFC in the ZPE using a novel, within-subject assessment in participants with either an acquired (lesion patients) or degenerative (behavioural-variant frontotemporal dementia patients) lesion of the vmPFC, and age-matched healthy controls. All participants were asked to make a series of choices between pairs of items that varied in price. One choice trial involved an equal decrease of both item prices, such that one of the items was priced zero. In contrast to controls, patients with both vmPFC-lesion and behavioural-variant frontotemporal dementia showed marked reductions in zero-related changes of preference in pairs of gift-cards, but not for pairs of food items. Our findings suggest that affective evaluations driving the ZPE are altered in patients with focal or degenerative damage to the vmPFC. This supports the notion of a key role of the vmPFC in the ZPE and, more generally, the importance of this region in value-based affective decision-making. Our findings also highlight the potential utility of affective heuristic tasks in future clinical assessments.